AC Electrical Properties of a NiFe-Layered Double Hydroxide with an Exceptionally Low Charge Density - Tosapol Maluangnont; Saichon Sriphan; Kanokwan Chaithaweep; Naratip Vittayakorn; Rattanawadee Ploy Wijitwongwan; Makoto Ogawa (The Journal of Physical Chemistry C, 2025)
Single-phase NiFe-layered double hydroxides (LDHs) with low and high charge densities [CD, 0.85 vs 3.23 nm–2; FeIII/(NiII + FeIII) = 0.05 and 0.25] were successfully prepared via urea-assisted coprecipitation in aqueous glycerol under hydrothermal conditions. The low-CD NiFe-LDH showed decreased apparent activation energies of water evaporation and of glycerol thermal decomposition, suggesting diminished intercalate/layer interactions relative to the high-CD one. The alternating current properties of the two samples were investigated on frequency and temperature domains by several formalisms that highlight distinct electrical components. We found that the low-CD NiFe-LDH exhibited smaller static dielectric permittivity and slower relaxation time, and it was less conducting than the high-CD analog. Complex plane analyses revealed the temperature dependence of resistance and capacitance at grain and grain boundary, varying by 7–10 orders of magnitude due to water loss and glycerol loss (∼9.5 and 11.3 wt %, respectively). Our work provides insights into intercalate dynamics in a low charge density LDH, which is difficult to obtain so far, from ambient to elevated temperatures (RT–250 °C) prior to decarbonation and layer collapse.
Keywords: Layered Double Hydroxides Synthesis and Applications; Supercapacitor Materials and Fabrication; Advanced Battery Materials and Technologies